Thrombotic events in acute promyelocytic leukemia. Issue 4 (April 2015) - Mitrovic, Mirjana; Suvajdzic, Nada; Elezovic, Ivo; Bogdanovic, Andrija; Djordjevic, Valentina; Miljic, Predrag; Djunic, Irena; Gvozdenov, Maja; Colovic, Natasa; Virijevic, Marijana; Lekovic, Danijela; Vidovic, Ana; et al.
Abstract Introduction Thrombotic events (TE) appear to be more common in acute promyelocytic leukemia (APL) than in other acute leukemias, with reported prevalence ranging from 2 to10-15%. Materials and Methods We retrospectively analyzed the data on TE appearance in 63 APL patients. Results TE occured in 13 (20.6%) cases, four arterial (6.3%) and nine venous (14.3%). TE were more frequently diagnosed after initiation of weekly D-dimer monitoring (7 TE during 20 months vs 6 during 76 months, P = 0.032). Patients with and without venous thrombosis were significantly different regarding female/male ratio (P = 0.046), PT (P = 0.022), aPTT (P = 0.044), ISTH DIC score (P = 0.001), bcr3 (P = 0.02) and FLT3-ITD (P = 0.028) mutation. The most significant risk factor for venous TE occurrence in multivariate analysis was FLT3-ITD mutation (P = 0.034). PAI-1 4G/4G polymorphism was five times more frequent in patients with venous TE than without it (P = 0.05). Regarding risk factors for arterial TE we failed to identify any. Conclusions We have demonstrated that APL-related TE rate is higher than previously reported and that weekly D-dimer monitoring might help to identify patients with silent thrombosis. Moreover, our study suggests a possible relationship between venous TE occurrence and several laboratory findings (PT, aPTT, ISTH DIC score, bcr3 isoform, FLT3-ITD mutation and PAI 4G/4G). Prophylactic use of heparin might be considered in patients with ISTH DIC score < 5, bcr3 isoform, FLT3-ITD mutation and PAI 4G/4G.